Syntactic translation strategies for retaining parallelism in the Arabic translation of Moby Dick - Syed Abdullah, Syed Nurulakla; Jabak, Omar Osman (Universiti Malaysia Sarawak, 2016)
The present study examines strategies for translating parallelism and factors in retaining parallelism in the Arabic translation of the novel of “Moby Dick”. Analysis is conducted on two sets of data taken from the English novel “Moby Dick” written by Melville in 1851 and its Arabic translation ‘Mūbī Dīk’ by ʻAbbās (1980). This qualitative research is guided by Chesterman’s (1997) syntactic strategy model, and contrastive analysis (CA) is also performed. The contrastive analysis is carried out using a coding procedure based on themes and taxonomies in the acquired data constructed by the researchers. The result shows that, based on Chesterman’s (1997) model, the translator of the above-mentioned novel employed three strategies, namely, literal translation, clause structure change and transposition to maintain parallelism in the Arabic translation of the English novel.